Research on Torque Ripple Minimization of Double-stator Switched Reluctance Motor Using Finite Element Method - Gupta T.D.; Chaudhary K. (My University, 2025)
Double-stator switched reluctance motors (DSSRMs) possesses high torque/power density. However, these machines have high torque ripples in the commutation region because the outgoing and incoming phase torques reduce significantly in this region. Shifting the stator/rotor surfaces can increase the torque production in this region, subsequently reducing the torque ripples. This paper investigates the angular shift in stator/rotor surfaces to reduce the torque ripples in a 12/10/12 pole DSSRM. A comparative analysis is done with the individual shift of rotor surfaces, stator surfaces and then the simultaneous shift of stator-rotor surfaces. Furthermore, the impact of the different surface shifts on the radial stress of stator poles, radial and tangential forces on rotor segments and the influence on the motor performance are investigated. To predict the behaviour of different surface shifts, finite-element modeling and simulation are performed in ANSYS/MAXWELL software. Simulation results envisage that shifting in stator/rotor surfaces can effectively reduce torque ripples in DSSRM. © 2021. AECE. All Rights Reserved.